Pengaruh Sanksi Pajak, Pengetahuan Perpajakan Dan Kesadaran Wajib Pajak Terhadap Kepatuhan Wajib Pajak Bumi Dan Bangunan Di Kecamatan Guntur Kabupaten Demak - Rahayu, Dwi; Septi Adila, Frinda; Sufa Kefi, Batista (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2023)
Tax, as one of the largest contributors to state income, including land and building tax, which is a source of Original Regional Income in Demak Regency, is expected to improve the welfare of the people in the area, so that taxpayer compliance in Demak Regency must continue to be improved. This research aims to determine the influence of tax sanctions, tax knowledge, and taxpayer awareness on taxpayer compliance in Guntur District, Demak Regency.The research population is all taxpayers who pay Land and Building Tax (PBB) in Guntur District, Demak Regency in 2022. The research sample was 40, determined using the solvin formula, and selected randomly. The data used is primary data, with data collection techniques using questionnaires, data analysis used is multiple linear regression analysis.The research results show that: (1) Tax sanctions have a significant positive effect on taxpayer compliance, (2) Tax knowledge has a positive and significant effect on taxpayer compliance, and (3) Taxpayer awareness has a positive and significant effect on taxpayer compliance. It is hoped that these results can be input for the Demak Regency Government to continue to educate its people to comply with paying taxes, and become a reference for similar research for future researchers.